O212 IVOR LEWIS ESOPHAGECTOMY AFTER SLEEVE GASTRECTOMY: THE USE OF GASTRIC CONDUIT IS STILL POSSIBLE. (23rd November 2019) - Pallabazzer, Giovanni; Santi, Stefano; Solito, Biagio; D'Imporzano, Simone; Belluomini, Mario Antonio
Abstract: Aim: This paper is a case report about a patient with esophageal adenocarcinoma that occurred many years after laparoscopic sleeve gastrectomy (LSG), highlighting the technical difficulties that an esophagectomy after bariatric surgery entails. Background and methods: Esophagectomy for cancer is a complex operation than can be associated with significance morbidity and mortality. Options for esophagectomy include either partial esophagectomy with an intrathoracic (Ivor-Lewis resection) or a total esophagectomy with a neck anastomosis (three field technique described by McKeown or transhiatal esophagectomy described by Orringer). These operations can be performed by minimally invasive techniques and currently selection of these procedure depend on the tumor's location and the patient's history of prior abdominal o thoracic surgery. Obesity is a leading preventable cause of death worldwide and bariatric surgery is widely accepted as the best treatment for obesity and obesity related diseases [1]. The Roux-en Y gastric bypass has become the gold standard procedure but LSG has been gradually accepted as an important bariatric surgical procedure due to low morbidity and mortality rates, improvements of obesity-related comorbidities and short learning curve for surgeons. Planned esophagectomy in patients with history of bariatric surgery can be complex due to the altered gastrointestinal anatomy, representing a surgical challenge. Results: A 53-year-old, obese woman with a body mass index of 43.7 kg/m2 underwent LSG in June 2010. Her comorbidities included ipertension treated by ACE inhibitors, but she didn't complain of GERD. The procedure was uneventful, without postoperative complications. She lost 50 kg in two years. She has actually a body mass index of 30.6 kg/m2. She underwent a gastroscopy in January 2017 for pyrosis and chest pain that demonstrated an ulcerated polyp of the distal esophagus. The esophageal biopsies diagnosed an adenocarcinoma. Staging computed tomography, endoscopic ultrasonography classified it as stage T2N0Mx. The patient also performed a double contrast barium enema. She underwent esophagectomy after the decision of the tumor board. Operative technique Five 10-mm abdominal trocars were used to dissect and isolate the gastric tubule and to perform lymphadenectomy. The stomach was mobilized by dividing the adhesions with ultrasonic coagulating shears (Figure 1). Kocher maneuver was performed. The stomach was retracted superiorly, and the left gastric vessels were identified and divided. Lymphadenectomy of the celiac trunk and along the hepatic artery and splenic artery was then performed. The gastrohepatic ligament was divided, and the right and left crura of the diaphragm were dissected. The gastric tube was completed by dividing the stomach with an articulating linear stapler (Echelon FlexTM 60 mm, Ethicon Endo-Surgery®, NJ, US), starting alongside the lesser curvature, 3 cm above the first and second lower vascular arcades ('crow's foot') of the lesser curve, with a creation of new stomach pouch of about 5 cm width. The gastric vascularization was made on clinical grounds by inspection of the gastric serosa (Figure 2) and it was checked by fluorescence after injection of indocyanine green (Figure 3a and 3b). A feeding jejunostomy tube was placed. Thoracotomy was performed at the fifth intercostal space. The inferior pulmonary ligament was divided. The mediastinal pleura overlying the esophagus was dissected to the level of the azygos vein. The arch of the azygos vein was divided. The circumferential mobilization of the esophagus, with all surrounding tissue and the dissection of the intertracheobronchial lymph nodes, were performed. An esophagogastric anastomosis was constructed using a 25 mm circular stapler (Figure 4) at the level of the azygos vein. The esophagogastric anastomosis was covered with pleura to minimize the risk of leakage into the chest and to reduce tension on the anastomosis. After placement of a single 28F chest tube, the bronchi were aspirated, and the lung was inflated by anesthesiologic team. Postoperative course and follow up Postoperative management consisted of immediate extubation, early mobilization of the patient, bronchoscopy routinely performed during the first 2 postoperative days (POD), and enteral feeding via a jejunostomy tube starting on the second POD. A contrast swallow on the fifth POD was normal and the patient was discharged on the 10 th POD. The pathological examination classified the disease as stage T2N1Mx (1/30 retrieved lymph nodes). The follow up is 22 months and the patient is alive and disease-free. After 4 months anastomotic stenosis occurred, and the patient underwent three endoscopic dilatations with complete resolution of dysphagia. Conclusion: To our knowledge this is the first reported case of Ivor-Lewis esophagectomy after sleeve gastrectomy. The main concern in patients underwent previous bariatric surgery is which reconstruction is possible to perform after esophagectomy: can the stomach be used as a conduit or coloplasty is needed? Typically, reconstruction is done with a tubularized gastric conduit perfused by the right gastroepiploic arcade so after LSG it would be impossible to use the stomach since this bariatric procedure consists of a left partial gastrectomy of the fundus and the body along the lesser curvature of the stomach. However, in our opinion, the stomach can or could be still used on the basis of four considerations: first, the location of the tumor; second, the interval between bariatric surgery and the onset of cancer; third, the level of the gastric transection in order to create the sleeve; fourth, the possibility to check gastric bloody supply by means of fluorescence and indocyanine dye. 1) After LSG the remaining stomach can be used as a gastric conduit for gastric pull-up, but its length is limited due to the previous resection of the fundus so middle or proximal esophageal cancer poses a difficult scenario as the remaining stomach will likely not able to be pulled up high enough to achieve a tension-free anastomosis. In this scenario, an option is to perform a colonic interposition between the esophagus and the remaining stomach. 2) It is known that ischemia of the gastric conduit, due to the division of the left gastric and short gastric vessels at the time of conduit creation, contributes to poor anastomotic healing, causing anastomotic leaks and strictures. Laparoscopic ischemic conditioning with ligation of these vessels prior to esophagectomy has been proposed to allow neovascularization of the proximal stomach to improve blood flow and decrease the incidence of anastomotic complications. The length of time required to provide an adequate increase in gastric perfusion to significantly improve anastomotic healing in clinical practice is unknown. Clinical trials utilizing short ischemic conditioning (IC) intervals of 4-7 days have failed to demonstrate significant improvements in anastomotic outcomes [2-3]. One single institution randomized trial with IC performed 2 weeks prior to esophagectomy demonstrated a trend toward lower anastomotic leak rates, compared to patients undergoing immediate reconstruction, but this did not reach statistical significance [4]. Only one clinical study has objectively demonstrated increased neovascularization in the proximal stomach after four months of IC [5]. The duration of IC may be critical to optimize its effect on anastomotic healing, so the long time passed between sleeve gastrectomy and esophagectomy might have conditioned the gastric sleeve and have increased the neovascularization along the gastric body, allowing a good perfusion and, in turn, the anastomotic healing (Figure 2 and 3a). 3) To date there is a lack of standardization regarding the surgical technique of LSG and one of the most controversial points in LSG is the distance from the pylorus at which the gastric division should begin. The 2012 expert panel agreed that the transection should begin 2-6 cm from the pylorus [6]. In the present case, transection of the stomach started 5 cm from the pylorus, preserving a portion of gastroepiploic arcade that, with a part of the right gastric arcade, ensured an adequate gastric blood flow. 4) Transposition of the gastric conduit from abdomen to chest during esophagectomy requires careful evaluation of blood supply that can be compromised after bariatric surgery. Evaluation of the blood supply of the gastric conduit has traditionally been made on clinical grounds by inspection of the gastric serosa. Since 2015, in an effort to reduce the risk of anastomotic leak, we employed the use of indocyanine green (ICG) fluorescence angiography. It's known that intraoperative real-time assessment of perfusion with ICG fluorescence imaging shows both the micro- and macrovasculature, providing the surgeon an overall picture of the status of the gastric conduit. Also, in this case, once the gastric tubule was dissected and left gastric vessels ligated, the vascularization was checked by fluorescence which clearly highlighted the origin of the gastroepiploic artery, interrupted 3 cm above the 'crow's foot' at the lesser gastric curve, providing real-time information about the good vascularization of the whole gastric sleeve and suggesting the possibility to use the stomach as a conduit. In conclusion, bariatric patients with esophageal cancer can pose a technical dilemma for surgical treatment, the use of gastric conduit is still possible but the surgeon has to understand the altered gastrointestinal anatomy, to consider the location of the tumor, the interval between bariatric surgery and the onset of cancer, the effect of IC on the neovascularization along the gastric body and the gastric bloody supply by means of fluorescence indocyanine dye.